PENGARUH PELATIHAN, KOMITMEN DAN KOMUNIKASI TERHADAP KINERJA GURU DI SMA NEGERI 4 MANDAU - Mely Dessiani; Jumiati Sasmita; Eka Armas Pailis (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2023)
This study aimed to determine the effect of training, commitment and communication on teacher performance at SMA Negeri 4 Mandau. The data collection technique used a questionnaire that was distributed to 73 teachers. The data obtained were analyzed using multiple linear regression analysis. Based on research analysis, it is known that training has a significant effect on performance. This is because the training time is appropriate and is carried out outside working hours so that teachers can focus entirely on training. Most of the training methods involve practice rather than lectures. The preparation of training supporting facilities and infrastructure is also good so that teachers can participate in training calmly and comfortably to improve their performance. Commitment has no significant effect on performance. Even though teachers have shown commitment to schools, academic activities, and students, the majority of teachers are still unable to accept and consider the 2013 curriculum to be much more efficient than the independent curriculum, even though teachers' commitment to accepting changes and understanding of this curriculum is an essential aspect of teacher performance assessment. Communication has a significant effect on performance. This is because teachers can express the meaning of the message correctly, have harmonious relationships with fellow teachers, and have a mutually motivating attitude to exchange experiences in overcoming teaching difficulties and learning problems experienced by students. Training, commitment, and communication together have a significant effect on performance. Teachers demonstrate good performance by conveying subjective student learning outcomes, as well as having good knowledge in handling the character and psychology of students who have difficulty learning so that they can understand and respond to the individual needs of each student